Ex-Drug Users' and Health Professionals' Perspectives About School-Based Drug Use Prevention Programs: A Qualitative Study - Teuku Tahlil; Aiyub Aiyub (Frontiers Media S.A., 2021)
Adolescents have become a prime target for drug dealers in various countries around the world, including in Indonesia. To reduce the high number of drug users amongst adolescents, effective drug prevention programs should be developed and implemented. The present study aimed to identify effective school-based drug prevention programs for adolescents from the perspectives of former drug users and health professionals. This qualitative research used Focus Group Discussions (FGDs) to collect the data. The study participants consisted of eight Ex-Drug Users (EDUs) and eight Health Professionals (HPs) from health educational institutions and health service settings that were selected through purposive sampling. Data analysis was performed using the qualitative content analysis. Five themes were identified from both EDUs and HPs, including the negative effects of drugs, the socialization of drug abuse, the rehabilitation of drug addicts, the partner collaboration, and the obstacles in preventing drug use. All participants agreed that the drug prevention programs such as school-based drug prevention programs are necessary in order to minimize the adverse effects of drug use. While EDUs tended to focus on the social and psychological effects of drugs, the HPs were more inclined toward the risks of diseases, social impacts, and economic problems of the drugs as the reasons for program importance. In terms of the intervention programs, both EDUs and HPs proposed conducting socialization through the use of active methods and agreed that rehabilitation as an effective way for addict students. Also, both groups of participants agreed on the significance of internal and external support, as well as coordination and collaboration to produce an effective and quality program. While the EDUs cited external factors as the main obstacle to the success of program implementation, the HPs mentioned internal factors of the users. School-based drug prevention programs are an important and potentially effective strategy to reduce the use and the effects of drug use among adolescents. The support of various relevant stakeholders is needed to further increase the effectiveness of the programs and eliminate possible barriers to the implementation of the intervention programs.